Load-carrying capacity of ultra-thin shells with and without CNTs reinforcement - Nguyen, Tan N. (2023)
Isotropic ultra-thin shells or membranes, as well as cable–membrane structures, cannot resist loads at the initial state and always require a form-finding process to reach the steady state. After this stage, they can work in a pure membrane state and quickly experience large deflection behavior, even with a small amplitude of load. This paper aims to improve the load-carrying capacity and strength of membrane structures via exploiting the advantages of functionally graded carbon-nanotube-reinforced composite (FG-CNTRC) material. In this work, the load-carrying capacity and nonlinear behavior of membrane structures with and without CNTs reinforcement are first investigated using a unified adaptive approach (UAA). As an advantage of UAA, both form finding and postbuckling analysis are performed conveniently and simultaneously based on a modified Riks method. Different from the classical membrane theory, the present theory (first-order shear deformation theory) simultaneously takes into account the membrane, shear and bending strains/stiffnesses of structures. Accordingly, the present formulation can be applied adaptively and naturally to various types of FG-CNTRC structures: plates, shells and membranes. A verification study is conducted to show the high accuracy of the present approach and formulation. Effects of CNTs distribution, volume fraction, thickness, curvature, radius-to-thickness and length-to-radius ratios on the form-finding and postbuckling behavior of FG-CNTRC membranes are particularly investigated. In particular, equilibrium paths of FG-CNTRC membrane structures are first provided in this paper.